HUBUNGAN AKTIVITAS FISIK TERHADAP OBESITAS SENTRAL PADA USIA DEWASA - Sari, Vera Permata; Herlina, Herlina; Zulfitri, Reni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Physical activity is a movement of the body that increases energy andÂ burning of calories. Less of physical activity it causes substance of food that enters in the body only buried in the body and occurs as fat at stomach so causes of central obesity. This study aims to determine the relationship of physical activity to central obesity in adulthood. The design of this study is descriptive correlation using cross sectional approach. The sample of this study is 82 employees of Rectorate Universitas of Riau Pekanbaru, it taken by using purposive sampling technique. The measuring instrument in this study used a physical activity questionnaire, and a tape measure meter to determine the value of central obesity that has been tested for validity and reliability. The results showed that the majority of respondents aged 36-45 years (56,1%), and male sex 47 people (57,3%). Physical activity conducted by majority respondents is low physical activity as much as 68 respondents (82,9%). The majority of respondents who are obese central is a high central obesity of 69 respondents (84,1%). The result of Chi Square statistic test showed that P value (0,009) < Î± (0,05) it can be concluded that there is significant correlation between physical activity to central obesity in adulthood. Based on the results of this study it is expected that civil staff to carry out physical activities outside of work so that they can release an energy and can reduce central obesity.Keywords: adult, Obesity central, physical activity